A matheuristic for routing real-world home service transport systems facilitating walking. (15th October 2015) - Fikar, Christian; Hirsch, Patrick
Abstract: This paper provides a solution procedure for a state-dependent real-world routing and scheduling problem motivated by challenges faced in the urban home service industry. A transport service delivers staff members of different qualification levels to clients and picks them up after completion of their services. The possibility to walk to clients, interdependencies, time windows, assignment constraints as well as mandatory working time and break regulations are considered. The introduced matheuristic consists of two stages, identifying potential walking-routes and optimising the transport system. The presented numerical studies are performed with real-world based instances from the Austrian Red Cross, a major home health care provider in Austria. The results show that implementing walking and pooling of trips in solution procedures decreases the number of required vehicles substantially. Graphical abstract: Highlights: A matheuristic for a home service routing and scheduling problem is introduced. Motivated by challenges of urbanisation, walking and trip pooling are considered. Results show potential for a more sustainable home service industry.